Performance of the GE-645 associative memory while Multics is in operation - Schroeder, Mike (Procedings of ACM SIGOPS Workshop on System Performance Evaluation, 1971)
The Multiplexed Information and Computing Service (Multics) of Project MAC at M.I.T. runs on a General Electric 645 computer system. The processors of this hardware system contain logic for both paging and segmentation of addressable memory. They directly accept two-part addresses of the form (segment number, word number) which they translate into absolute memory addresses through a series of indexed table lookups. To speed this address translation each processor contains a small, fast associative memory which remembers the most recently used address translation table entries. This paper reports the results of performance measurements on this associative memory. The measurements were made by attaching an electronic counter directly to a processor while Multics was in operation, and were taken for several associative memory sizes. The measurements show that for the observed load 16 associative registers are enough.